Hurdles NGO face when fostering education among indigenous communities in Chittagong Hill Tracts - Chowdhury, Mohua Roy; Abdul Rahman, Abdul Razak; Burhan, Nik Ahmad Sufian (MMU Press Multimedia University, 2022)
Education enables indigenous children to exercise and enjoy economic, social and cultural rights. However, they are often marginalized and discriminated against when it comes to accessing education as compared to the non-indigenous children. This is well reflected among the indigenous community children in Chittagong Hill Tracts (CHT) situated in Bangladesh. After the signing of the peace accord, several development programmes had been employed by NGOs to foster education among the indigenous children. However, despite their immense efforts, there still tends to be an inadequacy in the progress of these indigenous children’s education attainment. NGOs face several challenges when reaching out to the indigenous communities. Hence, to study the challenges that NGOs face, a qualitative approach was used to understand and investigate the broader picture. Purposive sampling was used to determine the informants and gain insights from the perspective of six chosen NGO officers followed by a thorough in-depth interview to further fulfil the objective of this research. Qualitative thematic analysis was the main approach to data analysis. The findings revealed that geographical barriers, the violent conflicts and the psychology of the indigenous community itself pose a challenge that affects the indigenous students’ attainment in education. The language barrier is also some of the other challenges NGOs face. Based on these findings, a few recommendations were developed followed by suggestions on other potential research topics that may open up a platform for better focus on the educational development aspect of indigenous children in CHT.